Ultrastructural observation of oocytes in six types of stony corals. Issue 4 (August 2016) - Tsai, Sujune; Chang, Wei-Chieh; Chavanich, Suchana; Viyakarn, Voranop; Lin, Chiahsin
Graphical abstract: In this study, the ultrastructure of the oocytes of six scleractinian coral species was observed by transmission electron microscopy in order to improve our understanding of the organelles involved in coral oocyte formation. In addition to improving our understanding of the basic biology of coral reproduction, the ensuing dataset is critical for conservation-oriented studies seeking to cryopreserve corals during these times of dramatic global climate change. Microstructure of yolk bodies. (a) E. gemmacea contained no specific particles inside yolk bodies, which may gradually develop from follicles (arrow). (b) Yolk bodies with a loose structure (arrow) and microparticle structures in O. lacera and (c) M. hispida . (d) Homogeneous structure containing strip-like lipid granules in the yolk bodies of G. fascicularis and vesicle containing (e) yolk body particles (arrow). Scale bar = 2 μm. yb, yolk bodies; v, vesicle. Highlights: Yolk bodies contain special microparticles that may be associated with differences in biosynthesized proteins and nutrient sources; as such, their composition varies widely. Galaxea fascicularis produced the most voluminous lipid granules, though the average number of such granules per oocyte was only 12. The small size and low density of lipid granules within Montipora incrassata oocytes may be attributed to the either presence of symbiotic algae or large yolk bodies. Vesicles of different sizes were present in coral oocytes, and yolk may be derived from the larger of such vesicles. Abstract: In this study, the ultrastructure of the oocytes of 6 types of scleractinian corals was observed by transmission electron microscopy (TEM). Moreover, histological and ultrastructural analyses were performed to improve our understanding of the organelles involved in coral oocyte formation. In all 6 stony coral species, the microvilli were tubular and directly grew from the surface of the oocyte membrane; yolk bodies, lipid granules, and cortical alveoli accounted for most of the volume inside the oocytes, suggesting that they are associated with energy storage and buoyancy. Clear differences were observed in the size of yolk bodies and lipid granules in the oocytes of the 6 stony coral species, which occupied approximately 55%–80% of the inner space of the oocytes. Galaxea fascicularis exhibited the largest lipid granule volume, but the oocytes contained only an average number of 12.45 lipid granules per unit area. Only Montipora incrassata oocytes contained symbiotic algae. The smallest size and proportion of lipid granules in M. incrassata oocytes may be attributed to the presence of symbiotic algae and large yolk bodies, which may help oocytes produce energy and function as a nutritional source. This study is crucial for improving the understanding of the basic biology of coral reproduction, and the ensuing datasets is critical for conservation-oriented studies seeking to cryopreserve corals during these times of dramatic global climate change.